Peran Sinergis Influencer Marketing, Brand Trust, dan Word of Mouth dalam Membentuk Minat Beli Smartphone Samsung - Muhammad Ro’uf Ilyasa’; Guruh Taufan Hariyadi; Roymon Panjaitan; Ariati Anomsari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The purpose of this study is to examine how influencer marketing, brand trust, and word of mouth drive consumer interest in purchasing Samsung smartphones. Purposive sampling was the sampling strategy used, and a questionnaire was employed to collect data from respondents interested in. The PLS-SEM data analysis method was conducted using SmartPLS 4.0. This study examines the direct effects of word-of-mouth, brand trust, and influencer marketing on purchase intention. The findings indicate that purchase intention is positively and significantly influenced by influencer marketing, brand trust, and word-of-mouth, with brand trust being the most crucial factor. Thus, it has been demonstrated that word of mouth, influencer marketing, and brand trust all contribute significantly to optimizing purchase intent for Samsung smartphones.